The differentiated approach to the choice of surgical treatment options in patients with metastatic lesions of long bones - Vyrva, Oleg; Golovina, Yanina; Malyk, Roman (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
Metastatic lesions of long bones (MLLB) are one of the most frequent pathologies among all bone tumor diseases. Objective: to substantiate and develop a differentiated approach to the choice of indications to authorities retain the surgical treatment of patients with metastatic lesions of long bones. Methods: the results of the examination and treatment of 104 patients with metastatic lesions of long bones. The main factors affecting the patients survive are the initial diagnosis, the amount of metastatic lesions of long bones, pathological fracture, relapse-free period of a period, visceral dissemination, histological type of tumor, the type of metastatic lesions of long bones, according to ASA class, age of the patient. With the help of the method of mathematical modeling of the mechanical properties comparison us «implant – bone» o f t he system i n different types o f replacement post-resection defects in proximal and distal femur metaphysis. Results: for to facilitate the prediction of survival of patients developed a computer program that make work-up data of the patient. The program determines the probability for a patient belonging to a survival group: I — up to 6 months, II — from 6 to 24 months, III — more than 2 years. Depending on the survival prognosis developed indications for surgical interventions and their types (palliative or radical). Justify the most effective methods of substitution of post-resection defects braid children due to the localization of metastatic lesions of long bones. Developed and implemented into practice the method of substitution of metaphysial defects of the distal femur using the metal construction. A tactics of surgical treatment of patients with primary metastatic lesions of long bones has been proposed. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: ’Times New Roman’; mso-fareast-font-family: ’Times New Roman’; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> the use of the proposed tactic of treatment of patients with metastatic lesions of long bones allows substantiate indications for surgical interventions and their specific type, to prevent unreasonable and, accordingly, repeated operations.